Visão contemporânea sobre pinos anatômicos - Guiotti, Flávia Angélica [UNESP] (2014)
As an alternative to improve the adaptation of prefabricated posts in flared canals and weakened roots, the option is for relining prefabricated pin, known as a technique of anatomical post. This technique, which can be made with composite resin increases the adjustment post to the walls of the canal and reduces the cementing line, causing the retaining post is less dependent on the mechanical properties of the cementing agent. This article aims to provide an overview of anatomical posts, specifically in the last two decades, based on studies extracted from Scielo, Scopus and Pubmed, referring to the following terms of MeSH Data Base: custom made fiber post, indirect fiber glass posts, root canal therapy and post and core tecnique. According to the literature review in this article, it can be concluded that this technique has been used by several authors and has been shown effective and promising, it creates an individualized retainer with better adaptation and decreased mechanical imbrication cementing line .